Study on quality assessment of child health care services in a district of Assam - Alpana P Rabha (Public Health Review: International Journal of Public Health Research, 2017)
Introduction: Children less than five years of age is a critical indicator of the well being of children. In order to reduce infant as well as under-five mortalityrate of children, Govt of India has initiated different health programmesas well as recommended Indian Public Health Standards for health care facilities to provide quality health care.Objective: To assess the quality of child health care services at health care facilitiesat primary and secondary level.Methodology: A cross-sectional study hadbeen conducted at CHCs, PHCs andS/Cs in Kamrup district of Assam. The data had been collected by quality assessment checklists and exit interview with the clients availing the child health services at the health care facilities.Results: The quality of child health care services was assessed by using a system approach-inputs, process and outputs.Therewereonly 66.66% availability of Obstetrics & gynaecologyspecialist and paediatrician. Physician were available in 33.33% of CHCs.The availability of trained personals was found to be inadequate in all the CHCs and PHCs. Most ofthe equipments and supplies were available in all the health care facilities. The child health care activities in areas of immunization and cold chain maintenance was found to be satisfactory.Conclusion: The quality of child health care services was found to be average at primary and secondary level.